Increase in thalamic cerebral blood flow is associated with antidepressant effects of ketamine in major depressive disorder. (14th September 2022) - Gärtner, Matti; de Rover, Mischa; Václavů, Lena; Scheidegger, Milan; van Osch, Matthias J. P.; Grimm, Simone
Abstract: Ketamine is a promising treatment option for patients with Major Depressive Disorder (MDD) and has become an important research tool to investigate antidepressant mechanisms of action. However, imaging studies attempting to characterise ketamine's mechanism of action using blood oxygen level-dependent signal (BOLD) imaging have yielded inconsistent results- at least partly due to intrinsic properties of the BOLD contrast, which measures a complex signal related to neural activity. To circumvent the limitations associated with the BOLD signal, we used arterial spin labelling (ASL) as an unambiguous marker of neuronal activity-related changes in cerebral blood flow (CBF). We measured CBF in 21 MDD patients at baseline and 24 h after receiving a single intravenous infusion of subanesthetic ketamine and examined relationships with clinical outcomes. Our findings demonstrate that increase in thalamus perfusion 24 h after ketamine administration is associated with greater improvement of depressive symptoms. Furthermore, lower thalamus perfusion at baseline is associated both with larger increases in perfusion 24 h after ketamine administration and with stronger reduction of depressive symptoms. These findings indicate that ASL is not only a useful tool to broaden our understanding of ketamine's mechanism of action but might also have the potential to inform treatment decisions based on CBF-defined regional disruptions.